Effects of morphine, pethidine and fentanyl on isolated rabbit trachea - Shen Jian-fan; Lin Ya-fang; Wu Qian-ping (Acta Pharmacologica Sinica, 2016)
Effects of morphine, pethidine and fentanyl on tension of isolated rabbit trachea were measured by electric field stimulation. Findings obtained were: 1) Morphine 53 mumol.L-1 increased markedly the trachea contraction (P < 0.01); 2) Fentanyl 1.9 mumol.L-1 decreased the trachea contraction (P < 0.05); 3) Pethidine 705 mumol.L-1 not only decreased markedly the trachea contraction (P < 0.01), but also relaxed the trachea; 4) Naloxone 2.2 mumol.L-1 had no influence on the trachea directly (P > 0.05), but reversed the effect of morphine on the trachea. The results indicated that the excitation of morphine receptor in trachea may be one of the mechanisms of the contraction of the trachea.